Nitrogen-doped coal-based graphene oxide as well as preparation method and application thereof
By introducing specific amounts and forms of nitrogen into coal-based graphene oxide, high catalytic activity nitrogen-doped coal-based graphene oxide is prepared, which solves the problems of insufficient catalytic activity and high cost of electrocatalytic preparation of ethanol in the prior art, and achieves efficient and economical catalyst preparation and application.
Patent Information
- Application Number
- CN202311404580.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-10-26
AI Technical Summary
The prior art lacks catalytic activity in the electrocatalytic preparation of ethanol in CO2, and is relatively expensive, and the preparation process is cumbersome. The amount of nitrogen-doped graphene is very low, which is difficult to reach or exceed 5%.
By introducing 5-12 wt% of nitrogen into coal-based graphene oxide, pyridine nitrogen accounts for 30-45 wt% of the total nitrogen element, nitrogen doping was performed by dielectric barrier discharge plasma etching to prepare nitrogen-doped coal-based graphene oxide with high catalytic activity as a support for preparing CO2 electrocatalytic preparation of ethanol.
It significantly improves the catalytic activity of CO2 electrocatalytic preparation of ethanol, reduces the preparation cost of catalysts, simplifies the preparation process, and realizes the efficient preparation of nitrogen-doped graphene, which is suitable for large-scale production.
Smart Images

Figure CN119898765A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparing ethanol by electrocatalytic reduction of CO2, and in particular to nitrogen-doped coal-based graphene oxide and a preparation method and application thereof. Background Art
[0002] The capture, utilization and storage (CCUS) of carbon dioxide (CO2) is a necessary way to reduce the CO2 emissions from existing coal-fired power, coal chemical, petrochemical and other industries. Since CO2 is a thermodynamically stable molecule, it is the result of the combustion of various carbon-containing chemicals. It can only be converted into other carbon compounds under harsh reaction conditions such as high temperature, high pressure, and high overpotential. The electrochemical method of reducing carbon dioxide has environmental advantages such as mild reaction conditions (normal temperature and pressure) and no secondary carbon emissions. This technology can convert CO2 into a variety of high-value-added chemical raw materials. It is a promising technology with large-scale application potential in the utilization of CO2, and the research enthusiasm continues to increase.
[0003] Depending on the catalyst used, CO2 electrocatalysis can produce a variety of different products, including C1 (carbon monoxide, formic acid, methanol, methane) and C2+ (ethylene, ethane, ethanol, propylene, n-propanol, etc.). Ethanol is an important chemical raw material. At the same time, as a high-value CO2 deep reduction product, ethanol is easy to separate, store and transport. Therefore, CO2 electrocatalysis to ethanol has a wide range of application scenarios.
[0004] In the electrocatalytic CO2 reduction process, the first step is the activation of the CO2 molecule, that is, it reacts with one electron to generate *CO2 at a reduction potential of -1.9 V relative to the standard hydrogen electrode. - Free radical intermediate. This step is difficult to occur because CO2 is a very stable linear molecule with low electron affinity. The cleavage of C=O requires 750.0 kJ mol -1 Energy is required for electrocatalytic CO2 reduction, so this step is often considered to be the rate-determining step of the electrocatalytic CO2 reduction reaction. In addition, the hydrogen evolution reaction in the electrolyte competes fiercely with the adsorption activation reaction of *CO. Therefore, in order to produce high-value-added ethanol, the most critical step is to convert CO2 into *CO.
[0005] Since the generation of multi-carbon (C2+) products requires complex multi-electron / proton coupling and CC coupling, the Faraday efficiency of C2+ products is low. Among various metal CO2RR electrocatalysts, copper is the only metal catalyst that has negative adsorption energy for *CO and positive adsorption energy for *H, so it can selectively reduce CO2 to various C2+ products with high added value. However, metal copper catalysts often have disadvantages such as wide product distribution, poor activity, low C2+ selectivity, and poor stability.
[0006] The bimetallic Cu-M tandem catalyst first reduces CO2 to *CO on the M catalyst, followed by CC coupling on Cu. Compared with direct reduction of CO2 to CO followed by CC coupling in the absence of M, the synergistic effect of the tandem mechanism increases the probability of CC coupling for the production of ethanol.
[0007] Each carbon atom in graphene is sp 2 The hybrid orbital forms a six-membered ring structure with five carbon atoms, and has excellent physical and chemical properties, large specific surface area, high electrical conductivity, adjustable molecular structure, acid and alkali resistance, etc. It is widely used as a carrier material for catalysts. In recent years, nitrogen-doped carbon materials have received widespread attention. There are currently a variety of methods for preparing graphene with different nitrogen contents, through in situ or non-in situ synthesis of nitrogen-doped graphene. However, existing preparation methods such as chemical vapor deposition and solvothermal methods have problems such as high cost and cumbersome preparation process. The amount of non-in situ nitrogen doping is very low, and it is difficult to reach or exceed 5%.
[0008] Patent application CN 115584525 A discloses a catalyst for electrocatalytic CO2 synthesis of multi-carbon products and its preparation method. The catalyst is CuInS with Cu-In dual active centers. 2-x The invention comprises the following steps: firstly, using a solvothermal reaction to synthesize In2S3 with a flower ball-shaped frill cluster structure, and then using an electrochemical ion replacement method to dope Cu into the defect sites of the flower ball-shaped frill cluster In2S3 to obtain CuInS with a Cu-In dual active center. 2-x Catalyst. The catalyst has both high electrocatalytic activity for CO2 RR and high selectivity for C2+ products, which can significantly improve the energy efficiency of CO2 utilization.
[0009] Patent CN 115094442 A discloses a method for preparing a copper-nickel bimetallic nitrogen-carbon material and its application in the electrochemical reduction of carbon dioxide. The preparation method is: using C3N4 and graphene oxide as carriers, using copper phthalocyanine and nickel phthalocyanine as metal sources and nitrogen sources, respectively, and introducing the nitrogen source by ammoniation of the substrate. The preparation method is simple, economical, and easy to operate. The obtained catalytic material has a rich layered structure, and the metal-based active sites are evenly distributed on both sides of the layered carrier. In the electrochemical reduction of CO2, it exhibits the characteristics of controllable adjustment of the ratio of CO and H2 in the reduction product.
[0010] Patent CN 112264081 B discloses a bimetallic-nitrogen-doped monolithic carbon-based electrocatalyst for electrochemical reduction of CO2 to ethanol and its preparation method. The precursor of the bimetallic-nitrogen-doped monolithic carbon-based electrocatalyst is prepared in one step at room temperature and pressure by competitive coordination crystallization method. The bimetallic-nitrogen-doped monolithic carbon-based electrocatalyst Fex Cu-NC is obtained by drying, pyrolysis in an inert atmosphere, acid washing, water washing and drying. The carbon-based electrocatalyst prepared by using bimetallic-nitrogen can not only effectively reduce the preparation cost of the catalyst, but also the synergistic effect between Fe and Cu bimetallic greatly improves the catalytic performance of the catalyst; it can be directly used as a gas diffusion electrode for testing the electrochemical CO2 reduction reaction, without the need for a binder, which is conducive to the electrochemical reaction.
[0011] At present, although there are some improved technologies for bimetallic catalysts based on nitrogen-doped graphene for CO2 electrocatalytic production of ethanol, how to further improve the catalytic activity of such catalysts in CO2 electrocatalytic production of ethanol and how to balance economic efficiency are still difficult problems that urgently need breakthroughs in this field. Summary of the invention
[0012] The present invention provides a nitrogen-doped coal-based graphene oxide and a preparation method and application thereof. The nitrogen-doped coal-based graphene oxide of the present invention is conducive to obtaining a catalyst with better catalytic activity in the electrocatalytic reduction of CO2 to prepare ethanol.
[0013] To achieve the purpose, the present invention provides the following technical solutions:
[0014] The first aspect of the present invention provides a method for preparing nitrogen-doped coal-based graphene oxide, comprising the following steps:
[0015] S1, providing coal-based graphene oxide;
[0016] S2, nitrogen-doping the coal-based graphene oxide to obtain nitrogen-doped coal-based graphene oxide, wherein the nitrogen-doped coal-based graphene oxide contains 5-12wt% of nitrogen, and the nitrogen element is at least partially present in the form of pyridinic nitrogen, and the pyridinic nitrogen accounts for 30-45wt% of the total amount of the nitrogen element.
[0017] The inventors have found that nitrogen-doped coal-based graphene oxide with a nitrogen content of 5-12wt% and a nitrogen doping content of 30-45wt% in the form of pyridine nitrogen can be used as a carrier to obtain a catalyst for preparing ethanol by electrocatalytic reduction of CO2 with better catalytic performance, especially the catalytic performance of electrocatalytic reduction of CO2 to prepare ethanol based on a catalyst of Cu-Ag active metal elements can be significantly improved; the nitrogen-doped coal-based graphene oxide provided by the present invention has a specific nitrogen doping content and a specific pyridine nitrogen doping amount, the carrier has a strong electron affinity, can be used as an adsorption site and activity for CO2, and can well adsorb and activate the reactant CO2; at the same time, N atoms can improve the conductivity of graphene, increase the positive charge density on adjacent carbon atoms, prevent protons from approaching, reduce the adsorption of hydrogen, weaken the competition of HER (hydrogen evolution reaction), and show a good ethanol yield and FE (Faraday efficiency).
[0018] Preferably, in step S1, the thickness of the coal-based graphene oxide is 0.8-1.2 nm, and the sheet diameter is 500 nm-1 μm; preferably, the purity of the coal-based graphene oxide is 98-100%, for example, 98.4-99.5%. The nitrogen-doped coal-based graphene oxide obtained by nitrogen-doping the preferred coal-based graphene oxide has a thinner sheet morphology and is conducive to obtaining better conductivity. It is subsequently used as a carrier for preparing a catalyst for preparing ethanol by electrocatalytic reduction of CO2, which is conducive to further improving the catalytic performance.
[0019] Preferably, in step S1, the coal-based graphene oxide contains 0.1-0.7wt% of S element and 0.3-1wt% of K element, for example, the K element content is 0.32wt%-1wt%. The inventors have found that using coal-based graphene oxide containing a small amount of S and K elements for subsequent nitrogen doping and then using it as a carrier in a catalyst for electrocatalytic reduction of CO2 to prepare ethanol can provide acidity and alkalinity for the catalyst and improve the catalyst performance. The coal-based graphene oxide obtained based on coal in the present invention contains a small amount of S and K, which are derived from impurities in the coal; preferably, the coal used in the present invention is sub-bituminous coal from the Shenfu Dongsheng mining area of the Shenhua base in China, belonging to the Early Jurassic and / or Middle Jurassic, and its chemical composition mainly includes: C 66-67wt%, H 3.5-3.8wt%, S 0.4-0.5wt%, N 0.9-1.2wt%, O 12-15wt%, P 0.001-0.005wt%, and K 0.2-0.5wt%.
[0020] In some embodiments, in step S2, the nitrogen element exists in the form of pyridinic nitrogen, amino nitrogen and pyrrolic nitrogen, for example, the nitrogen doping form is pyridinic nitrogen, amino nitrogen and pyrrolic nitrogen. There is no particular restriction on the proportion of amino nitrogen and pyrrolic nitrogen in the total nitrogen content, but the proportion of pyridinic nitrogen must reach 30-45wt%.
[0021] In some preferred embodiments, in step S2, the nitrogen doping is performed by plasma etching, preferably, the plasma etching method is a dielectric barrier discharge plasma etching method;
[0022] Further preferably, the conditions for the nitrogen doping by dielectric barrier discharge (DBD) plasma etching method include: power of 20 to 300 W, nitrogen flow rate of 50 to 300 mL / min, discharge time of 10 to 240 min, and N2 purity of 99.0 to 100%; the nitrogen doping is preferably carried out at room temperature and pressure. The above nitrogen doping process is carried out in a DBD reactor, and the coal-based graphene oxide is contacted with a non-equilibrium nitrogen DC plasma arc to react, thereby doping N into the coal-based graphene oxide.
[0023] The present invention adopts plasma etching method, especially dielectric barrier discharge plasma etching method, to carry out nitrogen doping of coal-based graphene oxide, which does not require high temperature and high pressure conditions, has the characteristics of high efficiency and environmental friendliness, and can regulate the bonding form of the doped nitrogen element and the content of the nitrogen element by controlling the power, nitrogen flow rate and other conditions during the nitrogen doping process, thereby regulating and improving the performance of graphene, and easily obtaining nitrogen-doped graphene with controllable target nitrogen content and nitrogen doping position. When preparing nitrogen-doped graphene in the prior art, high temperature and high pressure conditions are often required, and there are defects such as uncontrollable nitrogen content and nitrogen doping position. The present invention can introduce a specific amount of nitrogen element and a specific amount of pyridine nitrogen at a specific position in the coal-based graphene oxide through the above-mentioned preferred method, which can significantly improve the performance of CO2 electrocatalysis to ethanol.
[0024] In some preferred implementations, step S1 includes the following steps:
[0025] S1.1, preparing coal-based graphite using coal as raw material;
[0026] S1.2, preparing the coal-based graphene oxide from the coal-based graphite by a Hummer method.
[0027] In step S1.1, the coal can be prepared into coal-based graphite by conventional processes in the art. Specifically, the raw coal is subjected to high-temperature graphitization to obtain the coal-based graphite; the coal can be crushed and screened before use, for example, 200-mesh coal powder is subjected to high-temperature graphitization; wherein the temperature for high-temperature graphitization is, for example, 2500-3000°C, the time is, for example, 1-5 hours, and it is carried out in an inert gas atmosphere.
[0028] In step S1.2, the Hummer method is well known to those skilled in the art and can be performed with reference to the existing Hummer method process. As a preferred embodiment, step S1.2 specifically includes the following steps:
[0029] S1.21, stirring the coal-based graphite and sodium nitrate in concentrated sulfuric acid to obtain a mixed liquid, and adding an oxidant to the mixed liquid for intercalation oxidation treatment; the oxidant is preferably potassium permanganate, and the concentration of the concentrated sulfuric acid is preferably 95-100wt%; the amount ratio of the concentrated sulfuric acid to the sodium nitrate is preferably (50-200):(1-3), unit mL / g; the mass ratio of the sodium nitrate to the coal-based graphite is preferably (1-4):(0.5-2); the mass ratio of the oxidant to the coal-based graphite is preferably (3-10):(0.5-3);
[0030] S1.22, adding a reducing agent to the reaction system to reduce the remaining oxidant; the reducing agent is preferably hydrogen peroxide, for example, 30 wt% hydrogen peroxide; the amount of hydrogen peroxide used is based on the ability to completely consume the residual oxidant in the reaction system; for example, in some embodiments, 2-6 mL of 30 wt% hydrogen peroxide is used relative to 5 g of potassium permanganate;
[0031] S1.23, filtering, washing and drying the obtained product to obtain the coal-based graphene oxide; the washing is preferably firstly washed with dilute hydrochloric acid until the pH of the filtrate is 7-8, and then washed with a large amount of deionized water until the pH of the filtrate is 6-7, and the concentration of the dilute hydrochloric acid is preferably 1-3 mol / L;
[0032] Further preferably, in step S1.21, after adding the oxidant, the temperature of the reaction system is controlled not to exceed 20°C and stirred for 30-60min, then the temperature is raised to 20-50°C and the stirring is continued for 2-5h, and then the temperature is raised to 90-100°C to carry out step S1.22. Specifically, after the temperature is raised to 90-100°C, a portion of deionized water is first slowly added and stirred, for example, for 15-30min, wherein the amount of deionized water is, for example, 50-100mL relative to 5g of the oxidant, and then the reducing agent is added, and the reducing agent can be added dropwise.
[0033] In some specific embodiments, in step S1.21, concentrated sulfuric acid and sodium nitrate may be mixed evenly to completely dissolve the sodium nitrate, for example, stirred for 10-30 minutes, and cooled in an ice water bath, for example, stirred for 5-10 minutes to cool the solution (the system temperature is not less than 5° C.). Then, coal-based graphite is added to the solution, and stirring is continued for 30-60 minutes to mix evenly to obtain a mixed liquid.
[0034] In step S1.23, the drying may be oven drying, for example, oven drying at 80-100°C.
[0035] Through the above steps S1.1 and S1.2, thin coal-based graphene oxide with a flake morphology can be obtained. Preferably, the thickness of the obtained coal-based graphene oxide is 0.8-1.2 nm, the flake diameter is 500 nm-1 μm, and the purity is 98-100%.
[0036] Preferably, the coal used in step S1.1 is subbituminous coal from the Shenfu Dongsheng mining area of the Shendong base in China, belonging to the Early Jurassic and / or Middle Jurassic, and its chemical composition mainly includes C 66-67wt%, H 3.5-3.8wt%, S 0.4-0.5wt%, N 0.9-1.2wt%, O 12-15wt%, P 0.001-0.005wt%, and K 0.2-0.5wt%. The preferred raw coal is used to prepare coal-based graphene oxide, specifically, by preparing through the above steps S1.1 and S1.2, it is easy to obtain coal-based graphene oxide containing 0.1-0.7wt% of S element and 0.3-1wt% of K element, and the nitrogen-doped coal-based graphene oxide prepared by the subsequent steps based on the coal-based graphene oxide is used as a carrier in the catalyst for preparing ethanol by electrocatalytic reduction of CO2, which can obtain better catalyst performance.
[0037] The present invention uses cheap and abundant coal as a raw material to prepare graphene, which reduces the cost of catalysts and is conducive to the large-scale production and application of nitrogen-doped coal-based graphene oxide.
[0038] The second aspect of the present invention further provides a nitrogen-doped coal-based graphene oxide, wherein the nitrogen-doped coal-based graphene oxide contains 5-12wt% of nitrogen, and the nitrogen is at least partially present in the form of pyridinic nitrogen, and the pyridinic nitrogen is 30-45wt% of the total amount of the nitrogen;
[0039] Preferably, the nitrogen-doped coal-based graphene oxide has a flake morphology;
[0040] Preferably, the nitrogen element exists in the form of pyridinic nitrogen, amino nitrogen and pyrrolic nitrogen;
[0041] Preferably, the nitrogen-doped coal-based graphene oxide is prepared by the preparation method described above. The contents of the preparation method can be referred to the above description and will not be repeated here.
[0042] The third aspect of the present invention further provides a nitrogen-doped graphene catalyst loaded with active metal elements, wherein the catalyst uses the nitrogen-doped coal-based graphene oxide prepared by the preparation method described above as a carrier or uses the nitrogen-doped coal-based graphene oxide described above as a carrier;
[0043] The active metal elements loaded on the carrier include Cu element and Ag element; the molar ratio of the Cu element to the Ag element is preferably (3-6):1.
[0044] By using the nitrogen-doped coal-based graphene oxide of the present invention as a carrier, in particular as a carrier of a CO2 electrochemical reduction catalyst for ethanol production based on active metal elements Cu and Ag, excellent catalytic performance can be obtained at a lower dosage of active components. Preferably, based on the total mass of the catalyst, the total content of CuO and Ag2O (active components) does not exceed 6%, for example, 1-6%, and the content of CuO does not exceed 5%, for example, 1-5%.
[0045] When the above catalyst is prepared using the nitrogen-doped coal-based graphene oxide provided by the present invention as a carrier, the carrier can well disperse the metal active components on its surface and expose more active sites; the nitrogen doping amount of 5-12wt% and the nitrogen in the form of pyridine nitrogen account for 30-45wt% in the carrier, and the nitrogen-doped sites have strong electron affinity, which can be used as adsorption sites and active sites of CO2, and well adsorb and activate the reactant CO2, which is conducive to in-situ reduction of CO2 to generate *CO active intermediates; at the same time, it can well anchor the metal active components, improve the dispersion of metal active components such as Cu, and then improve the activity per unit specific surface area, so that good catalytic activity can be obtained while greatly reducing the amount of metal active components (such as Cu and Ag), and cost reduction can be achieved at the same time. The above catalyst is prepared using the nitrogen-doped coal-based graphene oxide of the present invention as a carrier, and the doped nitrogen atoms can improve the conductivity of graphene, increase the positive charge density on adjacent carbon atoms, prevent protons from approaching, reduce the adsorption of hydrogen, weaken the competition of HER, and show good FE and ethanol yields. The above-mentioned catalyst obtained by using the nitrogen-doped coal-based graphene oxide as a carrier based on the present invention has significantly improved catalytic activity in the CO2 electrocatalytic production of ethanol catalyst.
[0046] The catalyst prepared by the present invention has improved activity in the electrocatalytic production of ethanol from CO2. For example, in some embodiments, at a potential of -1.2 V vs. RHE, the ethanol Faradaic efficiency at room temperature and pressure is greater than 90%, and the current density reaches, for example, 170 to 250 mA / cm 2 .
[0047] The fourth aspect of the present invention also provides a method for preparing the nitrogen-doped graphene catalyst loaded with active metal elements as described above, comprising the following steps:
[0048] The support is immersed in an aqueous solution of a soluble salt of the active metal element, then the solvent is removed, and calcined under a protective atmosphere to obtain the catalyst;
[0049] Preferably, the calcination conditions include: calcining at a calcination temperature of 400 to 600° C., preferably for 3 to 8 hours; preferably heating to the calcination temperature at a heating rate of 3 to 10° C. / min.
[0050] In the present invention, the inert gas or protective gas involved may be, for example, N2, Ar, He, etc.
[0051] Specifically, the soluble salt of the active metal element may be any soluble salt of the corresponding metal element conventionally used in the art, such as nitrate, sulfate, etc., and there is no particular limitation on this.
[0052] The fifth aspect of the present invention provides an application, in which the catalyst described above or the catalyst prepared by the preparation method described above is used in the electrocatalytic reduction of CO2 to produce ethanol, or the nitrogen-doped coal-based graphene oxide prepared by the preparation method described above or the nitrogen-doped coal-based graphene oxide described above is used in the preparation of a catalyst for the electrocatalytic reduction of CO2 to produce ethanol.
[0053] The technical solution provided by the present invention has the following beneficial effects:
[0054] 1. The present invention uses nitrogen-doped coal-based graphene oxide to obtain nitrogen-doped coal-based graphene oxide containing 5-12wt% of nitrogen and 30-45wt% of pyridinic nitrogen. The carrier is used to prepare a CO2 electroreduction catalyst for ethanol production, and a catalyst with excellent catalytic activity can be obtained at a relatively low dosage of active components.
[0055] 2. The present invention provides coal-based graphene based on coal, the raw materials are cheap and easy to obtain, the catalyst cost is low, and it is easy to achieve large-scale production. The preparation method of the present invention is simple, and the preparation of CO2 electroreduction catalyst to ethanol based on the carrier of the present invention can reduce the amount of active components, which is conducive to reducing costs.
[0056] 3. In a preferred embodiment, nitrogen atoms of appropriate content can be controllably doped on coal-based graphene at room temperature by plasma etching method. The CO2 electroreduction catalyst to ethanol prepared based on the obtained carrier can effectively stimulate the in-situ reduction of CO2 to generate *CO active intermediates, reduce the reaction energy barrier, and improve the efficiency of CO2 electrocatalysis.
[0057] 4. Using the nitrogen-doped coal-based graphene oxide provided by the present invention as a catalyst carrier can improve the dispersion of active components, increase the activity per unit specific surface area, and thus reduce the amount of active components used and reduce the cost of the catalyst.
[0058] 5. Compared with the prior art, the nitrogen-doped graphene CO2 electroreduction catalyst loaded with active metal elements Cu-Ag prepared by the present invention can achieve a higher ethanol yield and a higher Faraday efficiency at a lower active metal element content, and the entire preparation process has the characteristics of low cost and low energy consumption, and can be mass-produced.
[0059] 6. The nitrogen-doped graphene catalyst loaded with active metal elements provided by the present invention uses the nitrogen-doped coal-based graphene oxide of the present invention as a carrier, has a large specific surface area, can well disperse the active components, and has good conductivity, which is conducive to improving the electrocatalytic effect. Using the nitrogen-doped coal-based graphene oxide of the present invention as a carrier can well anchor the active components and is not easy to cause the active components to agglomerate, thereby helping to improve the activity per unit specific surface area of the active components, that is, it can achieve excellent catalytic effects with a small amount of active components. The electrocatalytic reduction of CO2 to prepare ethanol catalyst based on the nitrogen-doped coal-based graphene oxide of the present invention can promote the coupling of C=C bonds and improve the yield of FE and ethanol. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 The figure shows a schematic diagram of the synthesis route of a bimetallic supported N-doped graphene CO2 electrochemical reduction catalyst for ethanol production in one embodiment;
[0061] Figure 2 Shown is a transmission electron microscope image of coal-based graphene oxide in Example 1;
[0062] Figure 3 Shown is the N2 adsorption-desorption curve of coal-based graphene oxide in Example 1;
[0063] Figure 4 Shown is the infrared spectrum of coal-based graphene oxide in Example 1;
[0064] Figure 5 Shown is the XPS graph of nitrogen-doped coal-based graphene oxide in Example 1;
[0065] Figure 6 Shown is a scanning electron microscope image of nitrogen-doped coal-based graphene oxide in Example 1;
[0066] Figure 7 Shown is a scanning electron microscope image of the bimetallic nitrogen-doped coal-based graphene oxide catalyst for CO2 electrochemical reduction to ethanol in Example 1;
[0067] Figure 8 Shown is the Faradaic efficiency of ethanol at different electrode potentials measured in Example 1. DETAILED DESCRIPTION
[0068] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.
[0069] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.
[0070] Where specific experimental steps or conditions are not specified in the examples, the corresponding conventional experimental steps or conditions in the art can be used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be purchased commercially.
[0071] In the following examples, when the prepared catalyst is subjected to a catalytic activity test experiment in the electrocatalytic reduction of CO2 to produce ethanol, the reaction is carried out in a flow-type electrolytic cell. The preparation of the working electrode and the assembly process of the flow-type electrolytic cell include:
[0072] (1) Preparation of working electrode: 60 mg of catalyst material, 4 mL of isopropanol, and 240 uL of 5 wt% Nafion solution were mixed, and then ultrasonically dispersed for 60 min to obtain a dispersion; the dispersion was evenly sprayed on carbon paper with a microporous layer to obtain a working electrode; the catalyst loading on the working electrode was 1 mg / cm 2 ;
[0073] (2) A commercial flow electrolytic cell system of Gaoshi Ruilian is used as an electrochemical CO2 reduction reaction device, wherein the electrolyte solution is a KHCO3 aqueous solution with a concentration of 1 mol / L, and the working electrode is the working electrode prepared in step (1) with an effective area of 2×2 cm 2 , the counter electrode is a platinum electrode, and the reference electrode is a silver / silver chloride electrode;
[0074] (3) Assemble the three-electrode flow-type electrolytic cell system of step (2), use rubber pads to isolate each component, use a commercial anion exchange membrane (Forma, Germany) as an electrolyte diaphragm, and use a clamp to assemble the entire test system to ensure good air tightness.
[0075] The catalyst selectivity was tested by constant potential method, and the catalytic product was detected by gas chromatography. The instrument model was Agilent GC7890B gas chromatograph, the detector was thermal conductivity detector (TCD), the carrier gas was Ar, and the quantitative method was external standard method.
[0076] The potential in the present invention is measured by Ag / AgCl electrode and converted to reversible hydrogen electrode (RHE) by the following formula:
[0077] E(vs.RHE)=E(vs.Ag / AgCl)+0.21V+0.0591×pH
[0078] Wherein, V is the voltage, and pH is the pH value of the electrolyte (KHCO3 aqueous solution, 1 mol / L).
[0079] The Faradaic efficiency (FE) is calculated as follows:
[0080]
[0081] Wherein, FE is the Faraday efficiency, in %; Z is the number of electrons transferred to produce ethanol, and its value is 12; n is the number of moles of the target product ethanol produced in the electrolysis process, in mol; Qtotal is the total charge consumption in the electrolysis process, in C; F is the Faraday constant, 96485 C / mol.
[0082] In the following examples, the raw coal used is subbituminous coal from the Shenfu Dongsheng mining area of the Shendong base in China, belonging to the Early Jurassic period, and its chemical composition mainly includes C 66.14wt%, H 3.78wt%, S 0.41wt%, N 0.94wt%, O 12.45wt%, P0.003wt%, K 0.3wt%, and the balance is volatile matter.
[0083] Example 1
[0084] The raw coal is crushed and screened to obtain 200-mesh coal powder for later use.
[0085] S1, providing coal-based graphene oxide
[0086] S1.1, 100 g of coal powder is graphitized at high temperature in a tubular furnace and calcined at 2800°C for 2 h in a N2 atmosphere to obtain coal-based graphite.
[0087] S1.2, preparing the coal-based graphene oxide from the coal-based graphite by a Hummer method:
[0088] S1.21, add 100mL of concentrated sulfuric acid (concentration is 98wt%) and 2g of sodium nitrate into a beaker successively, stir for 30min to dissolve all the sodium nitrate in the concentrated sulfuric acid, and place it in an ice bath and stir for 10min to cool the solution (the system temperature is not lower than 5°C).
[0089] Add 1g of the prepared coal-based graphite into the beaker and continue stirring for 60min to mix evenly to obtain a mixed liquid. Then, slowly add 5g of potassium permanganate into the mixed liquid, control the temperature of the reaction liquid not to exceed 20°C, and stir for 60min; then heat the water bath to 35°C and keep stirring at this temperature for 4h. Then heat to 98°C, slowly add 100mL of deionized water, and stir magnetically for 30min.
[0090] S1.22, then add 6 mL of 30 wt% hydrogen peroxide solution dropwise into the reaction system.
[0091] S1.23, filter the obtained reaction product, then wash the product with 2 mol / L dilute hydrochloric acid until the pH value of the filtrate is 7.5, and then wash with a large amount of deionized water until the pH value of the filtrate is between 6 and 7; then dry the washed product at 100°C to obtain coal-based graphene oxide.
[0092] The transmission electron microscope image of the prepared coal-based graphene oxide is shown in Figure 2 ,from Figure 2 It can be seen that the coal-based graphene oxide has a flake morphology. The thickness of the obtained coal-based graphene oxide is 0.8nm, the flake diameter is 1μm, and the specific surface area is 352.4m 2 / g, pore size is 6.5nm. The chemical composition of coal-based graphene oxide was tested by XRF, the purity was 99.43%, containing a small amount of S and K, S content was 0.25wt%, K content was 0.32wt%. Figure 3 It can be seen that the prepared coal-based graphene oxide has typical mesoporous channels. Figure 4 It can be seen that the prepared coal-based graphene oxide has no other impurity functional groups.
[0093] S2, Preparation of nitrogen-doped coal-based graphene oxide
[0094] Using the DBD plasma etching method, 1 g of coal-based graphene oxide dried in step S1.23 was placed in a dielectric barrier discharge reactor, and N2 was continuously introduced at a flow rate of 100 mL / min. The N2 purity was 99.9%. The dielectric barrier discharge reactor was turned on, the discharge time was 50 min, and the dielectric barrier discharge (DBD) plasma power was 100 W to obtain nitrogen-doped coal-based graphene oxide material.
[0095] from Figure 5 It can be seen from the XPS graph that nitrogen is successfully incorporated into coal-based graphene oxide, with a total nitrogen content of 10.8wt%. Nitrogen exists in the form of pyridinic nitrogen, amino nitrogen and pyrrolic nitrogen, of which pyridinic nitrogen accounts for 44.3wt% of the total nitrogen content, amino nitrogen accounts for 18.9wt% of the total nitrogen content, and pyrrolic nitrogen accounts for 36.8wt% of the total nitrogen content. Figure 6 It can be seen that the prepared nitrogen-doped coal-based graphene oxide has a flake-like morphology.
[0096] S3, Preparation of Cu-Ag supported nitrogen-doped graphene catalyst
[0097] Using the impregnation method, 500 μL of 1 mol / L copper sulfate aqueous solution, 1000 μL of 0.125 mol / L silver nitrate aqueous solution and 200 mL of deionized water were measured to prepare a mixed solution, and the mixed solution was added to 1 g of the nitrogen-doped coal-based graphene oxide obtained in step S2, stirred, and rotary evaporated to dryness at 120°C; then calcined in a N2 atmosphere under the following conditions: heating to 450°C at a heating rate of 5°C / min, and calcined at 450°C for 5h to obtain a Cu-Ag-loaded nitrogen-doped graphene catalyst.
[0098] The catalyst was subjected to XRF analysis, and the results showed that based on the total mass of the catalyst, the total content of active components (CuO and Ag2O) was 5.8wt%, the CuO content was 4.6wt%, and the molar ratio of Cu to Ag was 5.78:1.
[0099] from Figure 7 It can be seen that the active components of Cu and Ag are evenly distributed on the catalyst surface with small particle size and no agglomeration.
[0100] The Cu-Ag-supported nitrogen-doped graphene catalyst prepared in Example 1 was tested for catalytic activity in the electrocatalytic reduction of CO2 to produce ethanol. Figure 8 It can be seen that with the increase of electrode potential, the Faradaic efficiency of ethanol gradually increases. At -1.2 V vs. RHE potential, the Faradaic efficiency of ethanol reaches 92% and the current density is 236 mA / cm 2 .
[0101] Example 2
[0102] The raw coal is crushed and screened to obtain 200-mesh coal powder for later use.
[0103] S1, providing coal-based graphene oxide
[0104] S1.1, 100 g of coal powder is graphitized at high temperature in a tubular furnace and calcined at 2500°C in a N2 atmosphere for 2 h to obtain coal-based graphite.
[0105] S1.2, preparing the coal-based graphene oxide from the coal-based graphite by a Hummer method:
[0106] S1.21, add 100mL of concentrated sulfuric acid (concentration is 95wt%) and 3g of sodium nitrate into a beaker successively, stir for 30min to dissolve all the sodium nitrate in the concentrated sulfuric acid, and place it in an ice bath and stir for 20min to cool the solution (the system temperature is not lower than 5°C).
[0107] Add 1g of the prepared coal-based graphite into the beaker and continue stirring for 80 minutes to mix it evenly to obtain a mixed liquid. Then, slowly add 10g of potassium permanganate into the mixed liquid, control the temperature of the reaction liquid not to exceed 20°C, and stir for 60 minutes; then heat the water bath to 30°C and keep it at this temperature for 5 hours while stirring continuously. Then heat it to 100°C, slowly add 120mL of deionized water, and stir magnetically for 40 minutes.
[0108] S1.22, then add 8 mL of 30 wt% hydrogen peroxide solution dropwise into the reaction system.
[0109] S1.23, filtering the obtained reaction product, and then washing the product with 2 mol / L dilute hydrochloric acid until the pH value of the filtrate is 7.8, and then washing with a large amount of deionized water until the pH value of the filtrate is between 6 and 7; then drying the washed product at 100°C to obtain coal-based graphene oxide.
[0110] The obtained coal-based graphene oxide was subjected to transmission electron microscopy and showed a flake morphology. The thickness of the obtained coal-based graphene oxide was 1.2nm, the flake diameter was 800nm, and the specific surface area was 324.7m 2 / g, pore size is 7.2nm. The chemical composition of coal-based graphene oxide was detected by XRF, the purity was 99.45%, containing a small amount of S and K, S content was 0.1wt%, K content was 0.45wt%.
[0111] S2, Preparation of nitrogen-doped coal-based graphene oxide
[0112] Using the DBD plasma etching method, 1 g of coal-based graphene oxide dried in step S1.23 was placed in a dielectric barrier discharge reactor, and N2 was continuously introduced at a flow rate of 50 mL / min. The N2 purity was 99.9%. The dielectric barrier discharge reactor was turned on, the discharge time was 10 min, and the dielectric barrier discharge (DBD) plasma power was 100 W to obtain nitrogen-doped coal-based graphene oxide material.
[0113] According to the test, the total nitrogen content in the nitrogen-doped coal-based graphene oxide material is 8.6wt%, and the nitrogen exists in the form of pyridinic nitrogen, amino nitrogen and pyrrolic nitrogen, of which pyridinic nitrogen accounts for 31.6wt% of the total nitrogen content, amino nitrogen accounts for 21.9wt% of the total nitrogen content, and pyrrolic nitrogen accounts for 46.5wt% of the total nitrogen content. The prepared nitrogen-doped coal-based graphene oxide has a flaky morphology.
[0114] S3, Preparation of Cu-Ag supported nitrogen-doped graphene catalyst
[0115] Using the impregnation method, 500 μL of 1 mol / L copper sulfate aqueous solution, 800 μL of 0.125 mol / L silver nitrate aqueous solution and 200 mL of deionized water were measured to prepare a mixed solution, and the mixed solution was added to 1 g of the nitrogen-doped coal-based graphene oxide obtained in step S2, stirred, and rotary evaporated to dryness at 120°C; then calcined in a N2 atmosphere under the following conditions: heating to 400°C at a heating rate of 5°C / min, and calcined at 400°C for 6h to obtain a Cu-Ag-loaded nitrogen-doped graphene catalyst.
[0116] The catalyst was subjected to XRF analysis, and the results showed that based on the total mass of the catalyst, the total content of active components (CuO and Ag2O) was 5.16wt%, the CuO content was 4wt%, and the molar ratio of Cu to Ag was 5:1.
[0117] The Cu-Ag supported nitrogen-doped graphene catalyst prepared in Example 2 was tested for catalytic activity in the electrocatalytic reduction of CO2 to produce ethanol. The ethanol Faradaic efficiency was 90.5% at a potential of -1.2 V vs. RHE, and the current density was 186 mA / cm 2 .
[0118] Example 3
[0119] The raw coal is crushed and screened to obtain 200-mesh coal powder for later use.
[0120] S1, providing coal-based graphene oxide
[0121] S1.1, 100 g of coal powder is graphitized at high temperature in a tubular furnace and calcined at 3000°C for 2 h in a N2 atmosphere to obtain coal-based graphite.
[0122] S1.2, preparing the coal-based graphene oxide from the coal-based graphite by a Hummer method:
[0123] S1.21, add 100mL of concentrated sulfuric acid (concentration is 98.3wt%) and 1g of sodium nitrate into a beaker successively, stir for 30min to dissolve all the sodium nitrate in the concentrated sulfuric acid, and place it in an ice bath and stir for 10min to cool the solution (the system temperature is not lower than 5°C).
[0124] Add 1g of the prepared coal-based graphite into the beaker and continue stirring for 60min to mix evenly to obtain a mixed liquid. Then, slowly add 3g of potassium permanganate into the mixed liquid, control the temperature of the reaction liquid not to exceed 20°C, and stir for 60min; then heat the water bath to 50°C and keep stirring at this temperature for 4h. Then heat to 100°C, slowly add 80mL of deionized water, and stir magnetically for 30min.
[0125] S1.22, then add 5 mL of 30 wt% hydrogen peroxide solution dropwise into the reaction system.
[0126] S1.23, filter the obtained reaction product, then wash the product with 2 mol / L dilute hydrochloric acid until the pH value of the filtrate is 8, and then wash with a large amount of deionized water until the pH value of the filtrate is between 6 and 7; then dry the washed product at 100°C to obtain coal-based graphene oxide.
[0127] The obtained coal-based graphene oxide was subjected to transmission electron microscopy and showed a flake morphology. The thickness of the obtained coal-based graphene oxide was 1.1 nm, the flake diameter was 520 nm, and the specific surface area was 328.7 m 2 / g, pore size is 6.9nm. The chemical composition of coal-based graphene oxide was detected by XRF, the purity was 98.4%, containing a small amount of S and K, S content was 0.68wt%, K content was 0.92wt%.
[0128] S2, Preparation of nitrogen-doped coal-based graphene oxide
[0129] Using the DBD plasma etching method, 1 g of coal-based graphene oxide dried in step S1.23 was placed in a dielectric barrier discharge reactor, and N2 was continuously introduced at a flow rate of 300 mL / min. The N2 purity was 99.9%. The dielectric barrier discharge reactor was turned on, the discharge time was 240 min, and the dielectric barrier discharge (DBD) plasma power was 100 W to obtain nitrogen-doped coal-based graphene oxide material.
[0130] According to the test, the total nitrogen content in the nitrogen-doped coal-based graphene oxide material is 12wt%, and the nitrogen exists in the form of pyridinic nitrogen, amino nitrogen and pyrrolic nitrogen, of which pyridinic nitrogen accounts for 42wt% of the total nitrogen content, amino nitrogen accounts for 22.1wt% of the total nitrogen content, and pyrrolic nitrogen accounts for 35.9wt% of the total nitrogen content. The prepared nitrogen-doped coal-based graphene oxide has a flaky morphology.
[0131] S3, Preparation of Cu-Ag supported nitrogen-doped graphene catalyst
[0132] Using the impregnation method, 500 μL of 1 mol / L copper sulfate aqueous solution, 900 μL of 0.125 mol / L silver nitrate aqueous solution and 300 mL of deionized water were measured to prepare a mixed solution, and the mixed solution was added to 1 g of the nitrogen-doped coal-based graphene oxide obtained in step S2, stirred, and rotary evaporated to dryness at 120°C; then calcined in a N2 atmosphere under the following conditions: heating to 600°C at a heating rate of 5°C / min, and calcined at 600°C for 3h to obtain a Cu-Ag-loaded nitrogen-doped graphene catalyst.
[0133] The catalyst was subjected to XRF analysis, and the results showed that based on the total mass of the catalyst, the total content of active components (CuO and Ag2O) was 5.3wt%, the CuO content was 4wt%, and the molar ratio of Cu to Ag was 4.5:1.
[0134] The Cu-Ag-supported nitrogen-doped graphene catalyst prepared in Example 3 was tested for catalytic activity in the electrocatalytic reduction of CO2 to produce ethanol. The ethanol Faradaic efficiency was 91.6% at a potential of -1.2 V vs. RHE, and the current density was 203 mA / cm 2 .
[0135] Comparative Example 1
[0136] The method was carried out with reference to Example 1, except that: in step S2, when preparing nitrogen-doped coal-based graphene oxide, the N2 flow rate was 100 mL / min, the N2 purity was 99.9%, the dielectric barrier discharge reactor was turned on, the discharge time was 2 min, and the dielectric barrier discharge (DBD) plasma power was 100 W. The rest was carried out with reference to Example 1.
[0137] According to the test, the total nitrogen content of the prepared nitrogen-doped coal-based graphene oxide is 2.3wt%, and pyridinic nitrogen accounts for 13.7wt% of the total nitrogen content.
[0138] Experimental results: The catalyst prepared in Comparative Example 1 was tested for catalytic activity with reference to Example 1. At a potential of -1.2 V vs. RHE, the ethanol Faraday efficiency was 85.3% and the current density was 178.3 mA / cm 2 .
[0139] Comparative Example 2
[0140] The experiment was carried out with reference to Example 1, except that step S2, i.e., nitrogen doping was not performed, and the coal-based graphene oxide prepared in step S1 was directly used as a carrier to carry out the loading experiment of copper and silver elements with reference to step S3 of Example 1.
[0141] Experimental results: The catalyst prepared in Comparative Example 2 was tested for catalytic activity with reference to Example 1. At a potential of -1.2 V vs. RHE, the ethanol Faraday efficiency was 63.4% and the current density was 128.9 mA / cm 2 .
[0142] Comparative Example 3
[0143] The catalyst is prepared by a co-precipitation method without using a carrier.
[0144] The catalyst is composed of copper and silver oxides. The molar ratio of copper to silver is the same as that in Example 1.
[0145] 50 mL of 1 mol / L copper sulfate aqueous solution, 100 mL of 0.125 mol / L silver nitrate aqueous solution and 200 mL of deionized water were measured to prepare a mixed solution. The mixed solution was heated to 55°C, 150 mL of 1 mol / L NaOH aqueous solution was added dropwise to react for 0.5 h, 5 g of ascorbic acid was added, reacted for 5 h, centrifuged, washed with deionized water 5 times, and dried at 80°C to obtain Cu x Ag y O2 catalyst.
[0146] Experimental results: The catalyst prepared in Comparative Example 3 was tested for catalytic activity with reference to Example 1. At a potential of -1.2 V vs. RHE, the ethanol Faraday efficiency was 33.9% and the current density was 67.5 mA / cm 2 .
[0147] Comparative Example 4
[0148] The process is carried out with reference to Example 1, except that in step S3, silver nitrate is replaced by barium nitrate. In the catalyst of this comparative example, the molar ratio of Cu to Ba is the same as the molar ratio of Cu to Ag in the catalyst of Example 1.
[0149] Experimental results: The catalyst prepared in Comparative Example 4 was tested for catalytic activity with reference to Example 1. At a potential of -1.2 V vs. RHE, the ethanol Faraday efficiency was 55.6% and the current density was 78.8 mA / cm 2 .
[0150] Comparative Example 5
[0151] The process was carried out with reference to Example 1, except that in step S3, no silver nitrate was used, and the active metal element in the obtained catalyst was only Cu. The content of CuO in the catalyst obtained in this comparative example was the same as that in Example 1.
[0152] Experimental results: The catalyst prepared in Comparative Example 5 was tested for catalytic activity with reference to Example 1. At a potential of -1.2 V vs. RHE, the ethanol Faraday efficiency was 2.7% and the current density was 24.8 mA / cm2 .
[0153] Table 1 - Catalyst activity test results at 1.2V vs. RHE potential
[0154]
[0155] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.
Claims
1. A method for preparing nitrogen-doped coal-based graphene oxide, characterized in that: The steps include: S1, providing coal-based graphene oxide; S2, nitrogen-doping the coal-based graphene oxide to obtain nitrogen-doped coal-based graphene oxide, wherein the nitrogen-doped coal-based graphene oxide contains 5-12wt% of nitrogen, and the nitrogen element is at least partially present in the form of pyridinic nitrogen, and the pyridinic nitrogen accounts for 30-45wt% of the total amount of the nitrogen element.
2. The preparation method according to claim 1, characterized in that: In step S1, the coal-based graphene oxide has a thickness of 0.8-1.2 nm and a sheet diameter of 500 nm-1 μm; preferably, the coal-based graphene oxide has a purity of 98-100%, such as 98.4-99.5%.
3. The preparation method according to claim 1 or 2, characterized in that: In step S1, the coal-based graphene oxide contains 0.1-0.7wt% of S element and 0.3-1wt% of K element, for example, the content of K element is 0.32wt%-1wt%.
4. The preparation method according to any one of claims 1 to 3, characterized in that In step S2, the nitrogen element exists in the form of pyridinic nitrogen, amino nitrogen and pyrrolic nitrogen.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In step S2, the nitrogen doping is performed by plasma etching, preferably, the plasma etching method is a dielectric barrier discharge plasma etching method; Further preferably, the conditions for performing the nitrogen doping by dielectric barrier discharge plasma etching include: power of 20 to 300 W, nitrogen flow rate of 50 to 300 mL / min, discharge time of 10 to 240 min, and N2 purity of 99.0 to 100%; the nitrogen doping is preferably performed at room temperature and pressure.
6. The preparation method according to any one of claims 1 to 5, characterized in that: Step S1 includes the following steps: S1.1, preparing coal-based graphite using coal as raw material; preferably, preparing the coal-based graphite by subjecting the coal to high-temperature graphite at a temperature of 2500-3000°C; The coal is preferably sub-bituminous coal from the Shenfu Dongsheng mining area, belonging to the Early Jurassic and / or Middle Jurassic, and its chemical composition mainly includes C 66-67wt%, H 3.5-3.8wt%, S 0.4-0.5wt%, N 0.9-1.2wt%, O 12-15wt%, P 0.001-0.005wt%, and K 0.2-0.5wt%; S1.2, preparing the coal-based graphene oxide from the coal-based graphite by a Hummer method; Preferably, the step S1.2 specifically includes the following steps: S1.21, stirring the coal-based graphite and sodium nitrate in concentrated sulfuric acid to obtain a mixed liquid, and adding an oxidant to the mixed liquid for intercalation oxidation treatment; the oxidant is preferably potassium permanganate, and the concentration of the concentrated sulfuric acid is preferably 95-100wt%; the amount ratio of the concentrated sulfuric acid to the sodium nitrate is preferably (50-200):(1-3), unit mL / g; the mass ratio of the sodium nitrate to the coal-based graphite is preferably (1-4):(0.5-2); the mass ratio of the oxidant to the coal-based graphite is preferably (3-10):(0.5-3); S1.22, adding a reducing agent to the reaction system to reduce the remaining oxidant; the reducing agent is preferably hydrogen peroxide; S1.23, filtering, washing and drying the obtained product to obtain the coal-based graphene oxide; the washing is preferably firstly washed with dilute hydrochloric acid until the pH of the filtrate is 7-8, and then washed with deionized water until the pH of the filtrate is 6-7, and the concentration of the dilute hydrochloric acid is preferably 1-3 mol / L; Further preferably, in step S1.21, after adding the oxidant, the temperature of the reaction system is controlled not to exceed 20°C and stirred for 30-60 minutes, then the temperature is raised to 20-50°C and stirring is continued for 2-5 hours, and then the temperature is raised to 90-100°C to carry out step S1.
22.
7. A nitrogen-doped coal-based graphene oxide, characterized in that: The nitrogen-doped coal-based graphene oxide contains 5-12 wt% of nitrogen, and the nitrogen is at least partially present in the form of pyridinic nitrogen, and the pyridinic nitrogen accounts for 30-45 wt% of the total amount of the nitrogen; Preferably, the nitrogen-doped coal-based graphene oxide has a flake morphology; Preferably, the nitrogen element exists in the form of pyridinic nitrogen, amino nitrogen and pyrrolic nitrogen; Preferably, the nitrogen-doped coal-based graphene oxide is prepared by the preparation method according to any one of claims 1 to 6.
8. A nitrogen-doped graphene catalyst loaded with active metal elements, characterized in that: The catalyst is supported by the nitrogen-doped coal-based graphene oxide prepared by the preparation method according to any one of claims 1 to 6 or the nitrogen-doped coal-based graphene oxide according to claim 7; The active metal elements loaded on the carrier include Cu and Ag; the molar ratio of the Cu and Ag elements is preferably (3-6):1; Preferably, based on the total mass of the catalyst, the total content of CuO and Ag2O is 1-6%, and the content of CuO is 1-5%.
9. The method for preparing the nitrogen-doped graphene catalyst loaded with active metal elements according to claim 8, characterized in that: The steps include: The support is impregnated in an aqueous solution of a soluble salt of the active metal element, then the solvent is removed, and calcined under a protective atmosphere to obtain the catalyst; Preferably, the calcination conditions include: calcining at a calcination temperature of 400 to 600° C., preferably for 3 to 8 hours; preferably heating to the calcination temperature at a heating rate of 3 to 10° C. / min.
10. An application, characterized in that: The catalyst described in claim 8 or the catalyst prepared by the preparation method described in claim 9 is used in the electrocatalytic reduction of CO2 to prepare ethanol, or the nitrogen-doped coal-based graphene oxide prepared by the preparation method described in any one of claims 1 to 6 or the nitrogen-doped coal-based graphene oxide described in claim 7 is used in the preparation of a catalyst for the electrocatalytic reduction of CO2 to prepare ethanol.
Citation Information
Patent Citations
Nitrogen-doped graphene oxide material and preparation method thereof
CN103803539A
Method for preparing cold plasma N-doped porous graphene
CN106219533A
Nitrogen-doped graphene, preparation method thereof and capacitor
CN108706578A
Bimetal-nitrogen doped integral carbon-based electrocatalyst for preparing ethanol by electrochemical reduction of CO2 and preparation method thereof
CN112264081A
Preparation method and application of lamellar Cu-based N-doped graphene catalyst
CN114836781A
Cited By
Catalyst for preparing carbon monoxide and hydrogen through coal cracking and preparation method thereof
CN121372427A